Study of Radioactivity in Bajaur Norite Exposed in the Himalayan Tectonic Zone of Northern Pakistan - Hannan Younis (MDPI AG, 2021)
Radioactivity in Granites of Pakistan systematically increases from south to north. The Ambella Granite found at the northern edge of Pakistan is highly radioactive. Radioactivity measurements made on, so called, Bajaur Granite, located in northern Pakistan, have been found to be lowest among all the granitic rock of the area. In order to find out the exact nature of Bajaur rocks, mineralogical studies were carried on rock chips and powdered samples. The Bajaur Norite contains plagioclase feldspar more than 45% as the chief constituent. Orthopyroxene and clinopyroxene are 27% and 18%. Quartz, biotite, and some opaque minerals are also found in accessory amounts. Bajaur Granite is in fact not a granite but Norite, which is rich in Na-Ca plagioclase series of feldspars. The plagioclase feldspar rich in Na-Ca are low in radioactivity. Moreover, the average gamma activities of <semantics>226</semantics>Ra, <semantics>232</semantics>Th, and <semantics>40</semantics>K (4.98 ± 0.13 Bqkg <semantics>−1</semantics>, 4.03 ± 0.31 Bqkg <semantics>−1</semantics>, 204.40 ± 4.72 Bqkg <semantics>−1</semantics> and a total of all three radionuclides are 214.00 ± 5.39 Bqkg <semantics>−1</semantics>) for Bajaur Norites are found too be much less than the average of the world’s Granites. Indoor and outdoor hazard indices of Bajaur Norite are much below building materials used throughout the world and largely beneath their criterion restrictions. As per radiations’ hazards are concerned, the Bajaur Norite as a building stone may be considered as the safest material available in the area that does not pose any radiological hazard.